Pengaruh Kualitas Produk Dan Online Customer Review Terhadap Keputusan Pembelian (Studi Pada Pembelian Produk Kosmetik Wardah Melalui Online di Universitas Islam Malang) - Putri, Fira Selfiana; Priyono, Achmad Agus; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this study is to examine and ascertain how online customer reviews and product quality affect people's decisions to buy Wardah cosmetic items. This study employs a quantitative method of explanatory research. Using the Malhotra formula, female students at the Islamic University of Malang were sampled, resulting in a sample of 85 respondents for this investigation. Multiple linear regression analysis is used in this research approach utilizing SPSS analytic tools. The F and t tests are used in hypothesis testing. The study's findings demonstrate that the decision to buy Wardah cosmetic goods online is significantly influenced by both product quality and online customer reviews. The decision to buy Wardah cosmetic items online is somewhat influenced by the product quality variable. On the other hand, the decision to buy Wardah cosmetic products online is not significantly influenced by the online customer review variable. Keywords: Product Quality, Online Customer Review and Purchasing Decisions